Dilatation of Superior Ophthalmic Vein and Visual Disturbance by Central Venous Stenosis: A Case Mimicking Cavernous Sinus Dural Arteriovenous Fistula - Young Hun Jeon; Kyung Sik Yi; Chi Hoon Choi; Yook Kim; Yeong Tae Park (대한영상의학회지, 2021)
Central venous stenosis is a relatively common complication in hemodialysis patients; however, jugular venous reflux (JVR) and increased intracranial pressure are rare, and associated progressive visual disturbance was reported in only a few cases. Here, we report a case of JVR with visual disturbance and increased intracranial pressure. Notably, the MRI was accompanied by a dilatation of the superior ophthalmic vein, which was mistaken for a cavernous sinus dural arteriovenous fistula (CSdAVF). The patient had JVR on time-of-flight MR angiography (TOF-MRA) and severe stenosis of the left brachiocephalic vein on conventional angiography. After balloon angioplasty for central venous stenosis, he was discharged after improvement of his visual disturbance. Although JVR due to central venous stenosis and CSdAVF might show similar symptoms, treatment plans are different. Therefore, it is important to distinguish radiologically based on a thorough review of MRI and TOF-MRA and confirm the central venous stenosis on cerebral angiography for the accurate diagnosis.